Peranan Guru Pendidikan Agama Kristen dan Budi Pekerti Melalui Pendekatan Norma Agama dan Perubahan Perilaku dalam Mengatasi Bullying Antar Siswa di SMPN Satu Atap-1 Katingan Tengah - Silvia Rahmelia; Stephanus Prihadi; Nopitha Nopitha (EDULEAD: Journal of Christian Education and Leadership, 2023)
Role of Christian religious education teachers is considered strategic in cultivate character and behavior of Christian students as an extension of God's hand in the world whose full of love. However, the current reality is inversely proportional to the bullying phenomena that occur in schools. Bullying among students that occurred at SMPN Satu Atap-1 Katingan Tengah motivated researchers to identify the role of Christian education teachers at that school in overcoming bullying through the approach of religious norms and behavior change. The aims of this research were to identify forms of bullying and describe the role and efforts of teachers in dealing with bullying at SMPN Satu Atap-1 Katingan Tengah. This research uses a qualitative approach with observation, interviews and documentation as data collection techniques. Results proved that the forms of student bullying behavior that occurred at  SMPN Satu Atap-1 Katingan Tengah were in the category of verbal and realtion/social bullying. Based on research findings, teachers have carried out roles and efforts such as 1) preparing several students to be appointed as "friends" for victims of bullying; 2) allocate time or special sessions to communicate with perpetrators/victims of bullying before subjects end; 3) give advice and direct bullying students to write a statement/commitment letter; 4) creating an anti-bullying environment consistently by voicing the content of religious values and norms in the ceremonial supervisor's speech session.AbstrakPeran Guru Pendidikan Agama Kristen (PAK) terbilang strategis dalam membentuk perilaku siswa Kristen yang penuh cinta kasih sebagai perpanjangan tangan Tuhan di dunia. Namun realita saat ini berbanding terbalik dengan banyaknya fenomena perundungan yang terjadi di sekolah. Perundungan antar siswa yang terjadi di SMPN Satu Atap-1 Katingan Tengah melatarbelakangi peneliti untuk mengidentifikasi peran guru PAK di sekolah tersebut dalam mengatasi perundungan melalui pendekatan norma agama dan perubahan perilaku. Tujuan dari penelitian ini adalah 1) mengidentifikasi bentuk-bentuk perilaku perundungan di SMPN Satu Atap-1 Katingan Tengah; 2) mendeskripsikan peran dan upaya guru PAK dalam mengatasi perundungan di SMPN Satu Atap-1 Katingan Tengah. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data berupa observasi, wawancara dan studi dokumentasi. Hasil penelitian membuktikan bahwa bentuk-bentuk perilaku perundungan siswa yang terjadi di SMPN Satu Atap-1 Katingan Tengah ialah dalam kategori perundungan lisan dan hubungan. Berdasarkan temuan penelitian, guru PAK telah melakukan peranan dan upaya seperti 1) mempersiapkan beberapa siswa untuk ditunjuk sebagai “sahabat” bagi siswa korban perundungan; 2) mengalokasikan waktu atau sesi khusus untuk berkomunikasi dengan pelaku dan korban perundungan sebelum berakhir mata pelajaran PAK; 3) memberi nasihat dan mengarahkan siswa pelaku perundungan untuk menulis surat pernyataan/surat komitmen; 4) menciptakan lingkungan anti bullying secara konsisten dengan menyuarakan muatan nilai dan norma agama pada sesi amanat pembina upacara.